Sustainable Heavy Goods Vehicle Electrification Strategies for Long-Haul Road Freight Transportation - G. Rohith; K. B. Devika; Prathyush P. Menon; Shankar C. Subramanian (IEEE Access, 2023)
Even though diesel-powered Heavy Goods Vehicles (HGVs) are major contributors of greenhouse gas emission, HGV electrification is still in its infancy owing to various challenges. Costlier and heavier batteries and lack of charging infrastructure along long routes are the major bottlenecks in the realisation of HGV electrification for long-haul freight transportation. In this regard, adopting technologies that can make HGV electrification viable is vital to aid the transportation sector decarbonisation. Benefiting from approaches such as the use of overhead catenary power, and conforming to operate in a platoon formation, it would be possible to considerably reduce the cost of HGV electrification and make it economically feasible. Utilising overhead catenary infrastructure would result in requiring economical charging infrastructure, shorter charging cycles, and smaller batteries, while not compromising on the overall payload of HGVs. HGVs in platoon formation result in energy consumption reduction and increased traffic throughput. This paper investigates the benefits of using overhead catenary-powered electric HGVs for freight transportation and also explores the advantages associated with electric HGV platoon formations on the same. The feasibility analysis has been done with the support of close to real physics-based electric HGV models on realistic operating scenarios adopting an in-service highway drive cycle. From the analysis, electric HGV platooning using overhead catenary as the power source was found to be economical with $≈ 10.4%$ reduction in electricity cost when compared to without platooning while devising electrification strategies for long-haul freight transportation.